Projected shifts in the spatio-temporal distribution of larval chub mackerel (Scomber japonicus) under climate change in the western North Pacific - Go, Seonggil; Jung, Sukgeun (Frontiers in Marine Science, 2025)
We projected the effects of the climate change on the abundance and biomass distribution of chub mackerel (Scomber japonicus) eggs and larvae by developing and applying an individual-based model (IBM) based on a regional ocean circulation model for the western North Pacific. While building upon established IBM frameworks, this study provides the first high-resolution projection of larval chub mackerel biomass and distribution under climate change in this region. Our IBM tentatively suggested that the distribution of chub mackerel larvae extended from the southern waters of the East China Sea to the Japanese coastal areas, the Korea Strait and Japan/East Sea, following the Tsushima warm current, a branch of the Kuroshio current. The larval chub mackerel biomass during the 2010s was higher from April to June, peaking in May, in the East China Sea. Despite the greater uncertainty, the preliminary results of our IBMs projected that, by the 2050s, the increased water temperature, driven by global warming, will increase the larval mackerel biomass and shift their distribution north to the Yellow Sea and the Japan/East Sea. To enhance the model performance, international collaborative research among regional countries is recommended, particularly for conducting comprehensive ichthyoplankton surveys in the western North Pacific and sharing fisheries data. We expect that our model projections will contribute to the development of fisheries policy and management plan for adaptation to climate change in the region.